Pengetahuan Pasien Tentang Diet Cairan dan Nutrisi pada Pasien Gagal Ginjal Kronik (GGK) Di Ruang Hemodialisa RSUD Kabupaten Indramayu Tahun 2017 - Hikmawati, Kitri (Jurnal Keperawatan Profesional, 2019)
Chronic renal failure is a clinical condition of kidney damage which can cause the body fails to maintain metabolism and fluid and electrolyte balance, which causes uremia and fluid build up. Knowledge of diet fluids management and nutrition in renal failure patient is important to know and for those who are determined to reduce the risk of kidney disorders.  The purpose of this research is to know the description of Patient’s Knowledge about Fluid and Nutrition Diet in Chronical Renal Failure (GGK) in hemodialysis room of RSUD Indramayu 2017 ". This research uses descriptive method, the population in this study for about 127 and  the sample in this study for about to 90 respondents in accordance with the inclusion criteria taken with  Consecutive Sampling Technique. Data collection using questionnaire. Data were analyzed by Product Moment statistic test, with significance α = 0,05. Based on the results of the study can be concluded that the knowledge of patients about diet fluids and nutrition for about 74 patients (82.2%) respondents who have good knowledge. This research as an input for nurse hemodialisa room expected nurses can modify the delivery of health information through media and interesting methods about diet fluids and nutrition.Keyword. Knowledge, Fluid and Nutrition Diet, CRF